Integrating Information in Built Environments: From Concept to Practice - Sanchez, AX (Routledge, 2017)
In an increasingly globalised built environment industry, achieving higher levels of integration across organisational and software boundaries can lead to improved economic, social and environmental outcomes. This book is the direct result of a collaborative global network of industry and academic researchers spread across nine countries as part of CIB’s (International Council for Research and Innovation in Building and Construction) Task Group 90 (TG90) Information Integration in Construction (IICON). The book provides a broad view of some of the opportunities and challenges brought by integrating information across organisational and system boundaries in the built environment industry. Chapters cover a large range of topics and are separated into three sections: resources, processes and added value. They provide a much-needed international perspective on a current global evolution in the industry and present leading original research and valuable lessons for researchers, industry practitioners, government clients and policy makers across the industry.